Should Aspiration of the Ankle With an Antibiotic Spacer Be Performed Prior to Reimplantation?. (July 2019) - Fuchs, Daniel; Parekh, Selene G.
Recommendation: We recommend that aspiration of the ankle with an antibiotic spacer prior to a second-stage reimplantation be strongly considered. Available studies indicate that a positive culture of the aspirate in this setting is predictive of residual infection, while a negative aspirate culture does not rule out infection and should be interpreted in light of other clinical indicators and laboratory values. Level of Evidence: Consensus. Delegate Vote: Agree: 92%, Disagree: 8%, Abstain: 0% (Super Majority, Strong Consensus)